EArly-OE: Atividades iniciais de engenharia de ontologias apoiadas em modelos de arquitetura organizacional - Detoni, Archimedes Alves (2019)
Nowadays, public and private organizations are being encouraged to improve the computerized support to their activities. They intend to integrate their Information Systems (ISs) and to use heterogeneous data from different sources in order to produce relevant and reliable information mainly to support their decision activities. This challenge is intensified by the growing complexity of the organizational architectures, which: internally require the orchestration of the interaction between various administrative units, which must act integrated and collaboratively in distinct business processes that cross various functional areas; and externally need to operate seamlessly with other organizations. However, organizational ISs often do not support properly their business processes and are not able to interoperate with external systems. It occurs because those ISs, in many cases, were developed gradually and independently, each with its own scope, data structure, and terminology. Therefore, we can note gaps related to the lack of integration, information sharing and adoption of common semantics between organizational ISs. In such scenarios, the current literature has been indicating the use of ontologies as interlanguage in order to establish a consensual conceptualization to be adopted in a given domain. Thus, enabling interoperability between ISs and the integration of data dispersed over several sources and ISs. For an ontology to fit the purpose of being a conceptual model capable of adequately representing a domain, Ontology Engineering (OE) methods generally indicate the need to select and utilize knowledge resources available in the context of the domain to be modeled. The selected knowledge resources should facilitate the identification of relevant concepts and relationships that must be present in ontology, thereby aiding ontology engineers to understand the problem domain. Focusing on this need, the present work proposes the systematized use of Enterprise Architecture (EA) models as resources in OE knowledge acquisition activities, once they are artifacts that provide a broad view of the elements which compose organizational domains, in particular the actors, processes, ISs and their interrelationships. Besides, EA models have increasingly being used in organizational environments to diagnose and design interoperability solutions. The investigation of this possible synergy between the OE and EA disciplines was started in an exploratory research that addressed a real problem of semantic interoperability into public security domain, whereby EArly-OE approach was developed - Enterprise Architecture-driven Early Ontology Engineering). Early-OE prescribes guidelines for using EA models elements as knowledge resources to support initial OE activities in structured process-rich organizational domains, e.g. definition of intended uses, potential users and requirements of an ontology. After being developed in that exploratory research applied to the public security domain, the approach was evaluated in an empirical study addressing a different domain, that of federal public budget and finances, by a group of participants with varied degrees of experience in developing ontologies